TATA KELOLA REKAM MEDIS BERBASIS ELEKTRONIK DALAM PEMBUATAN LAPORAN POLIKLINIK PASIEN RAWAT JALAN MENGGUNAKAN METODE AGILE - Mahdani, Resty; Yaumi, Tinika; Syahidin, Yuda; Yunengsih, Yuyun (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
This study aims to determine the governance of electronic-based medical records in making outpatient polyclinic reports using the agile method. The research method used is qualitative research with a descriptive approach. After analyzing the needs of the polyclinic reporting system, this study presents the steps of implementing the agile method of extreme programming. By using this method, a system that is adaptable, responsive, and focused on user needs can be developed. The results show that the use of the agile extreme programming method in the development of an electronic-based medical record system provides significant benefits. The process of planning, designing, coding, testing, and releasing is done iteratively and collaboratively. With this approach, the system can be continuously improved and adjusted to meet changing user needs and priorities. By describing the system design flowmap, context diagram, DFD and ERD to visualize the relationship between the components in the system that provides a systematic description of the stages of the report generation process. In conclusion, electronic-based medical record governance in making outpatient polyclinic reports using the agile extreme programming method is an effective and efficient approach. By combining the advantages of agile and extreme programming methods, an adaptive and responsive system can be developed.